Cattle, hogs, sheep and lambs, number on farms at June 1 of census years, Newfoundland and Labrador - Statistics Canada (Government of Canada, 2017)
This table contains 14 series, with data for years 1951 - 1981 (not all combinations necessarily have data for all years), and is no longer being released. This table contains data described by the following dimensions (Not all combinations are available): Geography (1 item: Newfoundland and Labrador); Type of livestock (14 items: Total cattle;Bulls;Cows for milk;Cows for beef; ...).